DIGITAL HORIZONS: NAVIGATING THE DYNAMIC LANDSCAPE OF MODERN MARKETING STRATEGIES - Shokhista Akhunova; Mokhirabonu Abdusattorova (Journals Park Publishing, 2024)
This article provides a comprehensive exploration of the ever-evolving realm of digital marketing and its impact on contemporary business strategies. The digital landscape has undergone rapid transformations, presenting marketers with both challenges and opportunities. This research delves into key aspects of digital marketing, including social media, content marketing, SEO, and data analytics. By analysing current trends and emerging technologies, the article aims to equip marketers with insights and strategies to effectively navigate the complex digital terrain. Practical examples and case studies illustrate successful implementations, offering a practical guide for businesses aiming to leverage digital platforms for enhanced visibility, engagement, and overall success. The research emphasizes the importance of adaptability and innovation in the digital era, urging marketers to embrace the dynamic nature of the digital landscape for sustained growth.
Keywords: Digital Marketing, Online Platforms, Contemporary Business, Marketing Strategies, Digital Revolution, Social Media, Content Marketing, Search Engine Optimization (SEO), Data Analytics, Consumer Behaviour.